2004
DOI: 10.1007/s00424-004-1319-9
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Mg2+ blocks endothelin-1-induced contraction through the inhibition of non-selective cation channels in coronary smooth muscle

Abstract: This study investigated the effects of changing the extracellular [Mg(2+)] ([Mg(2+)](o)) on endothelin-1 (ET-1)-induced contraction of rabbit coronary artery smooth muscle and the involvement of non-selective cation (NSC) channels in this response. Increased [Mg(2+)](o) shifted the concentration/contraction relationship curve of ET-1 to the right. In whole-cell patch clamp recordings, ET-1 (10(-7) M) induced a long-lasting inwards current (94.7+/-7.2 pA) that was inhibited by 8 mM [Mg(2+)](o) (45.3+/-4.4%) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 52 publications
1
16
1
Order By: Relevance
“…Therefore, we believe that the present study demonstrates genuine facilitation of NSC MS by ET-1. Nonetheless, considering previous report on ET-1 activated cationic currents in whole-cell recordings [37][38][39], the absence of channel activation by ET-1 alone in the present study is difficult to explain. The Ca 2+ -free condition might be supposed as a factor suppressing the activation of other cation channels by ET-1.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…Therefore, we believe that the present study demonstrates genuine facilitation of NSC MS by ET-1. Nonetheless, considering previous report on ET-1 activated cationic currents in whole-cell recordings [37][38][39], the absence of channel activation by ET-1 alone in the present study is difficult to explain. The Ca 2+ -free condition might be supposed as a factor suppressing the activation of other cation channels by ET-1.…”
Section: Discussioncontrasting
confidence: 46%
“…Previous studies have shown that ET-1 modulates various kinds of ion channels, e.g. it inhibits K ATP and K v channels [32][33][34], and stimulates L-type Ca 2+ channels, Cl − channels, and nonselective cation channels [23,[35][36][37][38][39]. These changes commonly imply that ET-1 has a depolarizing effect on vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…27 Several mechanisms for the vascular effects of magnesium have been proposed, including antioxidant actions, blockade of voltage-dependent calcium channels, release of NO, 28 and inhibition of ET-1 vasoconstriction. 29 However, if the severity or duration of ischemia were reduced by magnesium, one would expect a reduction in infarct volume, and this was not apparent in our data.…”
Section: Discussionmentioning
confidence: 52%
“…Single vascular smooth muscle cells were mechanically dispersed by triturating the arteries after two step enzyme treatment with papain (1 mg/ml) and collagenese (1.5 mg/ml) in Ca 2ϩ -free normal Tyrode solution as described previously. 18) Cells were kept at 4°C under Kraft-Brühe (KB) and used within the same day. KB solution contained (in mM): 70 KOH, 50 L-glutamate, 20 KH 2 PO 4 , 55 KCl, 20 taurine, 3 MgCl 2 , 20 glucose, 10 N-(2-hydroxyethyl)piperazine-N Ј-2-ethanesulfonic acid (HEPES), 0.5 EGTA adjusted to pH 7.3 with KOH.…”
Section: Methodsmentioning
confidence: 99%